PEMBANGUNAN APLIKASI SOSIALISASI PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Robet Diki Prasetiyo (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2020)
Dangue Fever (Demam Berdarah Dengue (DBD) is one of the main problems in Indonesia with the low value of the national larvae rate (Angka Bebas Jentik(ABJ) in 2017 of 46.7%. This value is still under the program target set by the government of ≥ 95%, so it needs socialization. With the development of android smartphone technology, socialization can be interestingly and easily understood. DBD socialization is more interesting with information, images and animated videos about DBD with the android-based application. The banefit of this application is people gain insight into DBD from prevention, symptoms, and treatment. This application development used the waterfall methodology and android studio software. In addition, After Effect CC was used to make animated videos. The research resulted in an android-bases DBD socialization application with a minimum version of Lollipop and short animations about DBD. Moreover, testing result using two version of android Lollipop and Pie shows that the application managed to run smoothly.